2003
DOI: 10.1177/1541204003255841
|View full text |Cite
|
Sign up to set email alerts
|

Blueprints for Violence Prevention

Abstract: A Message From OJJDPAs communities seek to prevent and control youth violence, they naturally look to the growing number of effective violence reduction programs that are being implemented across the Nation. How can they accurately assess the relative merits of these competing programs and determine the strategy best suited to meeting their local needs?Through the Blueprints for Violence Prevention Initiative, OJJDP provides information to communities on a broad array of violence prevention and intervention pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
168
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(174 citation statements)
references
References 60 publications
1
168
0
5
Order By: Relevance
“…Few programs have had rigorous evaluation to meet minimum standards of effectiveness (Mihalic et al 2001), but many successful or promising programs have addressed risk and protective factors across multiple domains. Researchers have found that narrowly focused interventions are likely to have limited impact unless they are part of a more comprehensive strategy (Dahlberg and Potter 2001;Farrell and Camou 2006;Farrell and Flannery 2006;Thornton et al 2000).…”
Section: Youth Violence Prevention Research: Identifying Risk and Promentioning
confidence: 99%
“…Few programs have had rigorous evaluation to meet minimum standards of effectiveness (Mihalic et al 2001), but many successful or promising programs have addressed risk and protective factors across multiple domains. Researchers have found that narrowly focused interventions are likely to have limited impact unless they are part of a more comprehensive strategy (Dahlberg and Potter 2001;Farrell and Camou 2006;Farrell and Flannery 2006;Thornton et al 2000).…”
Section: Youth Violence Prevention Research: Identifying Risk and Promentioning
confidence: 99%
“…Reviewers note challenges to the larger scale transport and implementation of effective treatments arise at multiple levels of the practice context (e.g., client, clinician, provider organization, service system) and may pertain to the nature of the treatment itself (Dane and Schneider 1998;Fixsen et al 2005;Mihalic and Irwin 2003;Schoenwald and Hoagwood 2001;Southam-Gerow et al 2008). Thus, achieving positive clinical outcomes goes beyond simply adopting an evidence-based intervention.…”
mentioning
confidence: 98%
“…With respect to evidence-based treatments, clinician adherence to treatment is one important indicator of implementation (Dane and Schneider 1998;Mihalic and Irwin 2003). Empirical associations between adherence and outcomes have been demonstrated for some treatments (see, e.g., Barber et al 1996;Barber et al 2006;Schoenwald 2008).…”
mentioning
confidence: 99%
“…Rather than supporting a patchwork of programs developed at the local level and typically not subject to careful evaluation, policy makers and funding agencies have all rallied around the concept of ''best practices'' and, in many cases, have made selection of evidence-based programs a requirement for funding (Guerra and Backer 2003). To facilitate this selection process, several youth violence prevention programs have been ''vetted'' as effective or promising based on careful reviews of outcome studies that include both efficacy and effectiveness trials (Chan et al 2004;Elliott 1998;Mihalic et al 2004). However, effective dissemination and implementation of evidence-based programming innovation also hinges on a number of assumptions, many of which remain problematic, in order to bridge the gap between science and practice (Wandersman 2003).…”
mentioning
confidence: 99%